Building and codifying a test for the skill of the bottom-facing service in volleyball for the third year students of the College of Physical Education and Sport Sciences - Hikmet Fadil, Asmaa (International Journal of Psychosocial Rehabilitation, 2020)
The research aims: to us E and legalization of testing skill-facing transmitter from the bottom in the plane of the ball for the students of the third stage in the Faculty of Physical Education and Sports Science for the University of Baghdad and determine degrees of standard levels for a test for skill-facing transmitter from the bottom in the plane of the ball for the students of the third stage in the College Physical Education and Sports Science , University of Baghdad for the year 2018-2019 , has a descriptive approach is a style survey being commensurate with the research problem , Identified the research sample purposively, and represented by students stage third in the Faculty of Physical Education and Sports Science for the University of Baghdad, totaling ( 73 ) students of distributors within (3) the people of the students, and formed a sample experiment reconnaissance of ( 15 ) students from outside the research sample , this has applied a test transmitter on ( 58 ) students , in order to determine the extent appropriate sample and initiate procedures for construction and included finding a scientific basis for the test , it has extracted the stairs of the amended standard and level on the main sample of ( 73 ) students after the extracted discriminatory force and its coefficient sprains within the legalization of testing procedures , to reach the following conclusions : build a test of skill transmitter from the bottom of the third students stage in the Faculty of Physical Education and Sports Science , University of Baghdad , there is a clear disparity in the levels of female students to the skill of under study by comparing the standard grades achieved levels normal distribution, and the recommendations of the need to build a skillful test that suits the abilities of female students to stand at the level of accuracy to have in order to create a good base in the volleyball game , sector Continuing the test prepared for assessing the accuracy of the students and for the aforementioned skill , and taking other tests on the technical skills that were not covered in the study.